Volt/Var Control of Electronic Distribution Network Based on Hierarchical Coordination - Zijie Huang; Kun Yu; Xingying Chen; Bu Xue; Liangxi Guo; Jiarou Li; Xiaolan Yang (Energies)
With the increasing penetration of high-proportion renewable energy sources and large-scale integration of power electronic devices, distribution networks are evolving towards power-electronized systems. The integration of high-proportion renewable energy introduces challenges such as bidirectional power flow and voltage violations. Unlike traditional voltage regulation devices with slow and discrete adjustment characteristics, power electronic devices can continuously and rapidly respond to voltage fluctuations in distribution networks. However, the integration of power electronic devices alters the operational paradigm of distribution networks, necessitating adaptive voltage-reactive power control methods tailored to the regulation characteristics of both power electronic devices and discrete equipment. To fully exploit the real-time regulation capabilities of power electronic devices, this paper established a hierarchical coordinated control model for power-electronized distribution networks to achieve optimal voltage-reactive power control. A three-stage hierarchical coordinated control architecture is proposed based on the distinct response speeds of different devices. A variable-slope linear droop control method based on voltage boundary parameter optimization is employed for real-time adjustment of soft open point (SOP) and inverter outputs. To address uncertainties in PV generation and load demand, a rolling optimization strategy is implemented for centralized control, supplemented by probabilistic modeling to generate multiple representative scenarios for hierarchical coordinated control. Case studies demonstrate optimized operational results across centralized and local control stages, with comparative analyses against existing voltage-reactive power control methods confirming the superiority of the proposed hierarchical coordinated control framework.